Kristologis yang Ada di Berbagai Konteks - agnes patrisia julita; Herianani Herianani; Yelsing Yelsing (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2025)
This study examines the development of Christological understanding in various cultural, historical and social contexts. Christology, as the study of the person and work of Jesus Christ, is central to the Christian faith and influences mission and religious practice. This study analyzes the basic understanding of Christology, its relationship to mission, its role in cultural contexts, and its development from the first Christian generation to contemporary life. Christological challenges identified include the tension between Jesus' humanity and divinity, and the contextualization of Christ's teachings in a pluralistic society. The findings show that a comprehensive christological understanding can bridge cultural differences and enrich interfaith dialog. The study also underscores the importance of applying Christological principles in daily life to create positive social impact and strengthen mission commitments.